Current and emerging therapies for managing hyperphagia and obesity in Prader‐Willi syndrome: A narrative review. (30th December 2019) - Tan, Qiming; Orsso, Camila E.; Deehan, Edward C.; Triador, Lucila; Field, Catherine J.; Tun, Hein Min; Han, Joan C.; Müller, Timo D.; Haqq, Andrea M.
Summary: In early childhood, individuals with Prader‐Willi syndrome (PWS) experience excess weight gain and severe hyperphagia with food compulsivity, which often leads to early onset morbid obesity. Effective treatments for appetite suppression and weight control are currently unavailable for PWS. Our aim to further understand the pathogenesis of PWS led us to carry out a comprehensive search of the current and emerging therapies for managing hyperphagia and extreme weight gain in PWS. A literature search was performed using PubMed and the following keywords: "PWS" AND "therapy" OR "[drug name]"; reference lists, pharmaceutical websites, and the ClinicalTrials.gov registry were also reviewed. Articles presenting data from current standard treatments in PWS and also clinical trials of pharmacological agents in the pipeline were selected. Current standard treatments include dietary restriction/modifications, exercise, and growth hormone replacement, which appear to have limited efficacy for appetite and weight control in patients with PWS. The long‐term safety and effectiveness of bariatric surgery in PWS remains unknown. However, many promising pharmacotherapies are in development and, if approved, will bring much needed choices into the PWS pharmacological armamentarium. With the progress that is currently being made in our understanding of PWS, an effective treatment may not be far off.